Polarity-Header Optical OFDM for Visible Light Communication Systems - Jie Lian; Maite Brandt-Pearce (IEEE Photonics Journal)
Orthogonal frequency division multiplexing (OFDM) is a candidate modulation technique to achieve high-speed data transmission in visible light communication systems that provide both illumination and downlink data transmission. This paper proposes a method called polarity-header optical OFDM (PHO-OFDM) specially designed to account for the nonlinear response of the LED transmitters. To make the transmitted signal positive, as required for intensity modulation and direct detection systems, a signal header containing the sign information of the bipolar OFDM signal is transmitted followed by the amplitude of the signal. The binary sign information can be encoded and transmitted via a few samples using $M$ -ary pulse-amplitude modulation. The amplitude of the OFDM signal that is larger than the maximum LED power is sent in a subsequent frame to reduce the nonlinear distortion due to peak-power clipping. Furthermore, illumination requirements are taken into account, and their effects on the system performance are discussed. This paper also considers the overhead cost of adding a cyclic prefix to minimize intersymbol interference in dispersive channels. Compared with state-of-the-art optical OFDM techniques, the proposed PHO-OFDM achieves a better BER performance and higher data throughput, and provides a larger illumination flexibility.